A cross-sectional study of health and wellbeing among newly settled refugee migrants in Sweden - The role of health literacy, social support and self-efficacy - Al-Adhami, Maissa; Berglund, Erik; Wångdahl, Josefin; Salari, Raziye (PLoS ONE, 2022)

Agreement between mothers', fathers', and teachers' ratings of behavioural and emotional problems in 3-5-year-old children - Fält, Elisabet; Wallby, Thomas; Sarkadi, Anna; Salari, Raziye; Fabian, Helena (PLoS ONE, 2018)

Attachment and trauma-informed programme to support forcibly displaced parents of youth in Sweden: Feasibility and preliminary outcomes of the eConnect Online programme - Kristen, Anna; Salari, Raziye; Moretti, Marlene M.; Osman, Fatumo (BMJ Open, 2023)
Keywords: Feasibility Studies; Health Services Accessibility; Adolescent; MENTAL HEALTH

Can extended health communication improve newly settled refugees’ health literacy? A quasi-experimental study from Sweden - Al-Adhami, Maissa; Durbeej, Natalie; Daryani, Achraf; Wångdahl, Josefin; Larsson, Elin C; Salari, Raziye (Health promotion international, 2024)
Keywords: epidemiology; evidence-based health promotion; health literacy; intervention; health education; health information

Child behaviour problems, parenting behaviours and parental adjustment in mothers and fathers in Sweden - Salari, Raziye; Wells, Michael B; Sarkadi, Anna (Scandinavian Journal of Public Health, 2014)
Keywords: Behaviour problems; mothers; fathers; preschool children; parenting

Direct marketing of parenting programs: Comparing a promotion-focused and a prevention-focused strategy - Salari, Raziye; Backman, Anna (European Journal of Public Health, 2017)

Facilitating implementation of an evidence-based method to assess the mental health of 3-5-year-old children at child health clinics: A mixed-methods process evaluation - Fält, Elisabet; Salari, Raziye; Fabian, Helena; Sarkadi, Anna (PLoS ONE, 2020)

Impact of a culturally tailored parenting programme on the mental health of Somali parents and children living in Sweden: A longitudinal cohort study - Osman, Fatumo; Vixner, Linda; Flacking, Renée; Klingberg-Allvin, Marie; Schön, Ulla-Karin; Salari, Raziye (BMJ Open, 2021)
Keywords: community child health; mental health; child & adolescent psychiatry; public health

Is the Strengths and Difficulties Questionnaire with a Trauma Supplement a valuable tool in screening refugee children for mental health problems? - Fängström, Karin; Dahlberg, Anton; Ådahl, Kajsa; Rask, Hanna; Salari, Raziye; Sarkadi, Anna; Durbeej, Natalie (Journal of Refugee Studies, 2019)
Keywords: Strengths and Difficulties Questionnaire; complex trauma; refugee children; mental health problems

Neuropsychological functioning and attachment representations in early school age as predictors of ADHD symptoms in late adolescence - Salari, Raziye; Bohlin, Gunilla; Rydell, Ann-Margret; Thorell, Lisa (Child Psychiatry & Human Development, 2017)
Keywords: Attachment; Neuropsychological functioning; Adolescence; ADHD symptoms

NICU parents' mental health: A comparative study with parents of term and healthy infants - Persson, Christine; Ericson, Jenny; Salari, Raziye; Eriksson, Mats H.; Flacking, Renée (Acta Paediatrica, 2023)
Keywords: neonatal care; NICU; mental health; parents; preterm infants

Parental monitoring in late adolescence: Relations to ADHD symptoms and longitudinal predictors - Salari, Raziye; Thorell, Lisa (Journal of Adolescence, 2015)
Keywords: Child disclosure; Conduct problems; ADHD; Adolescence; Parental knowledge; Parental monitoring

Preschool-level socio-economic deprivation in relation to emotional and behavioural problems among preschool children in Sweden - Durbeej, Natalie; Ssegonja, Richard; Salari, Raziye; Dahlberg, Anton; Fabian, Helena; Sarkadi, Anna (Scandinavian Journal of Public Health, 2024)
Keywords: emotional and behavioural problems; Socio-economic deprivation; preschool children; Strengths and Difficulties Questionnaire

”Putting words to their feelings”– civic communicators’ perceptions and experiences of an in-depth course on mental health for newly settled refugee migrants in Sweden - Al-Adhami, Maissa; Wångdahl, Josefin; Salari, Raziye; Åkerman, Eva (BMC Health Services Research, 2023)
Keywords: Mental health training; Refugee migrants; Health promotion; Mental health literacy; Sweden

Quality of couple relationship and associated factors in parents of NICU-cared infants during the first year after birth - Persson, Christine; Ericson, Jenny; Eriksson, Mats; Salari, Raziye; Flacking, Renée (Journal of Perinatology, 2024)
Objective: To describe factors associated with quality of couple relationships among parents of infants cared for in neonatal intensive care units (NICUs) 1 year after birth and examine the trajectory of the relationship quality compared to parents from maternity units (MUs). Study design: Longitudinally comparative cohort design. Parents answered surveys during the first year after discharge about the couple relationship, social support, and depressive symptoms. Results: Better social support and a hospital stay of 7–14 days were positively associated with the couple relationship in NICU mothers, whereas not having slept together with the partner and infant during hospitalization were negatively associated. Depressive symptoms were negatively associated with the relationship among NICU fathers. There were no differences in trajectory of the relationship quality between NICU and MU parents. Conclusion: To strengthen couple relationships, it could be important to improve social support, facilitate space and time for support, and enable togetherness during hospitalization.
CRIS-Team Scopus Importer:2024-12-13

Role of universal parenting programs in prevention - Salari, Raziye; Enebrink, Pia (Handbook of parenting and child development across the lifespan, 2018)

SDQ in the hands of fathers and preschool teachers—Psychometric properties in a non-clinical sample of 3–5-year-olds - Dahlberg, Anton; Ghaderi, Ata; Sarkadi, Anna; Salari, Raziye (Child Psychiatry & Human Development, 2019)
Keywords: Preschool children; Strengths and Difficulties Questionnaire (SDQ); Construct validity; Fathers; Confirmatory factor analysis (CFA)

Study preregistration: Individual participant data meta-analysis: Individual differences in mediators of parenting program effects on disruptive behavior - Melendez-Torres, G.J.; Backhaus, Sophia; Gardner, Frances; Scott, Stephen; European Parenting Program Research Consortium; Salari, Raziye; Leijten, Patty; et al. (Journal of the American Academy of Child and Adolescent Psychiatry, 2024)

Successful implementation of parenting support at preschool: An evaluation of Triple P in Sweden - Dahlberg, Anton; Salari, Raziye; Fängström, Karin; Fabian, Helena; Sarkadi, Anna (PLoS ONE, 2022)

Swedish norms for the Strengths and Difficulties Questionnaire for children 3–5 years rated by parents and preschool teachers - Dahlberg, Anton; Fält, Elisabet; Ghaderi, Ata; Sarkadi, Anna; Salari, Raziye (Scandinavian Journal of Psychology, 2020)
Keywords: preschool children; psychometrics; mental health; norms; Strengths and difficulties questionnaire; Sweden

Teaching Recovery Techniques: evaluation of a group intervention for unaccompanied refugee minors with symptoms of PTSD in Sweden - Sarkadi, Anna; Ådahl, Kajsa; Stenvall, Emma; Ssegonja, Richard; Batti, Hemrin; Gavra, Parthena; Fängström, Karin; Salari, Raziye (European Child & Adolescent Psychiatry, 2018)
In 2015, a total of 35,369 unaccompanied refugee minors (URMs) sought asylum in Sweden. In a previous study of 208 URMs, we found that 76% screened positive for PTSD. This study aimed to (1) evaluate the indicated prevention program Teaching Recovery Techniques (TRT) in a community setting and describe the program’s effects on symptoms of PTSD and depression in URMs; and (2) examine participants’ experiences of the program. The study included 10 groups. Methods for evaluation included the Children’s Revised Impact of Event Scale (CRIES-8) and the Montgomery–Åsberg Depression Rating Scale Self-report (MADRS-S) at baseline and at post-intervention. Qualitative interviews were conducted with 22 participating URMs to elicit their experiences. Pre- and post-measures were available for 46 participants. At baseline, 83% of the participants reported moderate or severe depression and 48% suicidal ideation or plans. Although more than half (62%) of the participants reported negative life events during the study period, both PTSD (CRIES-8) and depression (MADRS-S) symptoms decreased significantly after the intervention (p = 0.017, 95% CI − 5.55; − 0.58; and p < 0.001, 95% CI − 8.94; − 2.88, respectively). The qualitative content analysis resulted in six overall categories: social support, normalisation, valuable tools, comprehensibility, manageability, and meaningfulness when the youth described their experiences of the program, well reflecting TRT’s program theory. Overall, results indicate that TRT, delivered in a community setting, is a promising indicated preventive intervention for URMs with PTSD symptoms. This successful evaluation should be followed up with a controlled study.
Created from Fastlane, Scopus look-up
Keywords: Depression; Prevention; PTSD; Teaching Recovery Technique (TRT); Unaccompanied refugee minors

Using normalisation process theory to identify factors facilitating the scaling up of parenting programs for immigrant parents - Osman, Fatumo; Schön, Ulla Karin; Salari, Raziye (Frontiers in Psychology, 2024)
Objective: As most studies focus on the initial adaptation of culturally tailored parenting programs in real-world settings, scalability and sustainability remain understudied. In this study, we used normalization process theory (NPT) as a conceptual framework to identify and understand the contextual factors impacting the scalability and sustainability of a culturally tailored parenting program, Ladnaan, in three Swedish municipalities. Method: Nineteen managers, coordinators, and group leaders completed a survey and participated in individual or focus group interviews. Results: Our analyses showed that participants agreed on the need for the Ladnaan intervention among immigrant families. However, they were concerned that insufficient resources may hinder the recruitment and retention of parents, particularly as certain resources were allocated to the delivery of other, non-evidence-based interventions. Both managers and coordinators emphasized that embedding Ladnaan into everyday practice is conditioned on the collective work and engagement of all stakeholders, which will occur only if local authorities feel they own the program. The recruitment and retention of group leaders was mentioned as a key challenge in sustaining Ladnaan as the need for the program fluctuated over time. Conclusion: These findings highlight the importance of promoting evidence-based programs within the services available for forcibly displaced parents, and of coordinating efforts to scale up and sustain these programs.
CRIS-Team Scopus Importer:2025-02-04
Keywords: culturally tailored; immigrants; normalization process theory; parenting programs; parents; scaling up; sustainable implementation

Using the Health Belief Model to explain mothers’ and fathers’ intention to participate in universal parenting programs - Salari, Raziye; Filus, Ania (Prevention Science, 2017)
Keywords: Fathers; Intention to participate; Health Belief Model; Universal parenting programs; Mothers